Radiation risk of cancer from medical imaging in end stage kidney disease patients: Italian nationwide survey. (September 2016) - Vigna, Luca; Lizio, Domenico; Brambilla, Marco; De Mauri, Andreana; Zoccali, Carmine; Postorino, Maurizio
Abstract : Purpose: End Stage Kidney Disease patients are exposed to ionizing radiation during imaging studies. The variability in diagnostic imaging policies and the accompanying risk across Renal Units are unknown. We studied this variability at centre level and quantified the associated risks at patient level, by estimating the organ doses (HT ) and the Risk of exposure-induced cancer death (%) (REID). Materials and methods: Fourteen nephrology departments enrolled 739 patients on hemodialysis (HD) and 486 kidney transplant patients (KTP), recording the details of the radiological procedures performed over one year. HT were derived using Montecarlo based simulation software for conventional diagnostic radiology procedures and for Computed Tomography. H T were derived using tabulated conversion factors for cardiac interventional radiology and nuclear medicine procedures. Results: The average REID was 0.047 ± 0.12 % and the corresponding 5-years cancer risk attributable to ionizing radiation exposure was 1 every 424 patients. The median REID was 0.009% and the 3 rd quartile was 0.03%. The average REID was significantly higher in HD than in KTP (0.06 ± 0.13 i.e. 1:333 patients for 5-years vs 0.03 ± 0.09 i.e. 1:666 patients for 5-years; p < 0.001). The variation of average REID among participating centres was highly significant ( F = 3.23; p < 0.001) ranging from a minimum of 0.009% to a maximum of 0.09%. Conclusion: The excess cancer risk attributable to medical exposure is highly variable among centres (a tenfold variation), suggesting that protocols of individual patient's follow up with medical imaging are not standardized. On average, KTP have a lower exposure than HD patients (a twofold variation). Disclosure: None to declare.